Japanese Offshore Banking: Toward a World Financial Center in Tokyo - Robertson, Dario F. (Tufts Archival Research Center, 2005)
Volume 8, Issue 1. Winter As part of a movement toward deregulation and internationalization of the Japanese financial system, policymakers in Japan are preparing to establish an offshore banking unit (OB U), similar to those already operating in New York, London, Singapore and Hong Kong. In this article, Dario F. Robertson examines (1) the probable institutional form of the Tokyo OBU; (2) its macroeconomic implications; and (3) suggestions for appropriate changes in Japanese policies to be pursued after the establishment of the OBU. He argues that the creation of an offshore banking facility in Tokyo is a feasible and desirable intermediate policy that will move the Japanese financial system significantly, if not inexorably, closer to complete deregulation. Robertson concludes that institution of an OBU in Tokyo will establish Japan in its rightful place as the predominant Asian financial center.